Comparative morphometrics and ecology of a newly discovered population of tylototriton Vietnamensis from Northeastern Vietnam including remarks on species conservation - Bernardes, Marta (Deutsche Gesellschaf für Herpetologie und Terrarienkunde e.V. (DGHT), Mannheim, Germany, 2019)
Te genus Tylototriton has a restricted distribution in the eastern Himalayas region, central and southern China, and Indochina (Nishikawa et al. 2014, Yang et al. 2014, Le et al. 2015). Te number of newly discovered Tylototriton species has been continuously increasing (Nishikawa et al. 2013a, b, Nishikawa et al. 2014, Yang et al. 2014, Le et al. 2015, Phimmachak et al. 2015) although the taxonomic status of some species is still under debate (e.g., Zhang et al. 2007, Nishikawa et al. 2013b, Nishikawa et al. 2015). In Vietnam, fve species of this genus are recognized and two of them, T. vietnamensis and T. ziegleri, are endemic to this country. Te Vietnamese crocodile newt T. vietnamensis is currently known only from three localities in northern Vietnam, i.e., the Tay Yen Tu Nature Reserve located in Bac Giang Province (the type locality), the Mau Son Mountain in Lang Son Province, and the Xuan Son National Park in Phu To Province (Nguyen et al. 2009, Yuan et al. 2011). Bernardes et al. (2013) also reported this species from the eastern side of Yen Tu Mountain, within the Yen Tu Nature Reserve, Uong Bi District, Quang Ninh Province, located opposite of the type locality. Tese authors also used the Species Distribution Model (SDM) to predict the potential occurrence of further populations in northern Vietnam. Herein we report on a new population of T. vietnamensis from Dong Son – Ky Tuong Nature Reserve in Quang Ninh Province, whose existence was predicted by the SDM. In addition, we analysed the genetic distance between the newly discovered population and already known ones, and evaluated morphological characters and ecological adaptations at the new site in comparison with those from the type locality.